2014
DOI: 10.1159/000358917
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Processing in Adolescence: An Event-Related Potential Study of Age and Gender Differences

Abstract: Adolescence has frequently been characterized as a period of increased risk taking, which may be largely driven by maturational changes in neural areas that process incentives. To investigate age- and gender-related differences in reward processing, we recorded event-related potentials (ERPs) from 80 participants in a gambling game, in which monetary wins and losses were either large or small. We measured two ERP components: the feedback-related negativity (FRN) and the feedback P3 (fP3). The FRN was sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 63 publications
2
22
1
Order By: Relevance
“…Adolescents showed higher FRN amplitudes to losses than adults under all conditions, a finding that in general terms aligns with other studies that have found similar data where nonprobabilistic learning is involved and with those that indicate that adolescents experience higher sensitivity to external feedback than adults [8,9]. To the best of our knowledge, however, this is the first study to find differences between adolescents and adults related to FRN in reinforcement probabilistic learning.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Adolescents showed higher FRN amplitudes to losses than adults under all conditions, a finding that in general terms aligns with other studies that have found similar data where nonprobabilistic learning is involved and with those that indicate that adolescents experience higher sensitivity to external feedback than adults [8,9]. To the best of our knowledge, however, this is the first study to find differences between adolescents and adults related to FRN in reinforcement probabilistic learning.…”
Section: Discussionsupporting
confidence: 90%
“…Grose-Fifer et al [8] found similar results, and suggested that adolescents have less efficient processing when it comes to adjusting their behavior to feedback. Another study reported that FRN latency decreases over the course of adolescent development, between 10 and 17 years of age, suggesting an increasing dependency on internal compared with external representations in terms of directing behavior [20].…”
Section: Adults Adolescentsmentioning
confidence: 82%
See 3 more Smart Citations